Effects of structural fracture and in situ stress combination characteristics on the production of coalbed methane wells: A case in the Mabidong block, China - Zhou Zhang (Wiley, 2021)
Abstract Similar drilling, fracturing, and drainage techniques were adopted in the early stage of developing coalbed methane (CBM) in the Mabidong block, but the production of adjacent CBM wells was significantly different. The effects of coal seam depth, thickness, reservoir pressure, the ratio of desorption pressure and reservoir pressure, and gas content on the production of CBM wells are systematically studied. It is found that these parameters are not the critical control factors. The data of 107 observation points were obtained by using high‐precision structural fracture mapping technology, and four structural fracture development zones were delineated in the Mabidong block. Simultaneously, according to the in situ stress state, the Mabidong area is divided into an in situ stress tension state, and in situ stress compression state, and an in situ stress transition state. Based on structural fracture development and in situ stress state characteristics, four kinds of matching relationships are found: ① Structural fracture development and in situ stress state are tension or transition state. ② The structural fractures are developed, but the in situ stress state is in the compression state. ③ The structural fracture is not developed, and the in situ stress state is tension or transition state. ④ The structural fractures are not developed, and the in situ stress is in the compression state. The comprehensive analysis of the 19 CBM well production shows that the CBM well production is high when the structural fracture dense area and the in situ stress tension and transition area coincide, while the CBM well production is low when other matching relationships. The matching relationship's accuracy in controlling the CBM well production is 89%. The characteristics of structural fracture development and in situ stress state are the combined control factors of CBM well production in the Mabidong block.